2011
DOI: 10.1590/s0004-282x2011000600009
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, social support perception and seizure controllability perception in adolescents with epilepsy

Abstract: Objective: Compare the self-esteem of adolescents with epilepsy and adolescents without epilepsy and relate it to social support and seizure controllability perception. Method: The study sample consisted: case participants (34 subjects) attending the pediatric epilepsy clinic of University Hospital and control participants (30 subjects) from public schools in Campinas-SP. The instruments utilized were: identification card with demographic and epilepsy data, a semi-structured interview on aspects of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
3
12
0
5
Order By: Relevance
“…It has been noted the importance of psychosocial and psychiatric conditions and their influence in determining the well-being of individuals in a chronic medical condition 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted the importance of psychosocial and psychiatric conditions and their influence in determining the well-being of individuals in a chronic medical condition 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Siqueira et al 27 investigated aspects that show that these adolescents have good knowledge of epilepsy, good social support perception, perception of seizure control and no significant differences when compared with a control group in rates of self esteem. Cancian 30 observed that the same adolescents with epilepsy seem to have better coping with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…people seem to disappear. 40 In the past 2 years, because of my epilepsy and everything…the thought of suicide has been in my head…I'd say 4 to 8 times…once, I had the knife at my wrist and my mother came in and I just pretended I was drying it. 18 In interviews for work, I don't tell.…”
Section: Alertness To Mortalitymentioning
confidence: 99%
“…Boom, back with a vengeance. 40 Insurmountable side effects Some days it's really hard. Some days, when you don't feel good, when you're having to start out on a higher dosage of meds…And, trying to maintain, while your body's going through hell.…”
Section: Alertness To Mortalitymentioning
confidence: 99%
See 1 more Smart Citation